Kompetensi Guru dan Citra Merek terhadap Keputusan Mendaftar di PAUD Mutiara Bunda Karanganyar - Jasur Robiht Tri Wicaksono; Indra Hastuti; Nur Hadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This article evaluates the influence of teacher competence and brand image on parents' decisions in choosing PAUD Mutiara Bunda Karanganyar. Involving 92 respondents selected through purposive sampling, this study employs a quantitative descriptive method. The results of the multiple linear regression analysis indicate a positive and significant correlation between the two independent variables and the decision to enroll. These findings conclude that optimizing teacher capacity and institutional brand management simultaneously serve as primary determinants for parents in deciding upon an educational institution for their children. Therefore, it is recommended that the institution’s management continuously improve service quality as a strategic effort to gain public trust. Therefore, the management of Mutiara Bunda Karanganyar PAUD needs to maintain and improve teacher competency through continuous professional development and strengthen the institution's image management strategy to be able to meet parents' expectations and increase competitiveness amidst the development of the early childhood education industry.